Is Mossy Fiber Sprouting a Potential Therapeutic Target for Epilepsy? - Cavarsan, Clarissa F.; Malheiros, Jackeline; Hamani, Clement; Najm, Imad; Covolan, Luciene (Frontiers in Neurology, 2018)
Mesial temporal lobe epilepsy (MTLE) due to hippocampal sclerosis is one of the most frequent focal epilepsies in adults. It is characterized by focal seizures that begin in the hippocampus, sometimes spread to the insulo-perisylvian regions and may progress to secondary generalization. Morphological alterations in hippocampal sclerosis are well defined. Among them, hippocampal sclerosis is characterized by prominent cell loss in the hilus and CA1, and abnormal mossy fiber sprouting (granular cell axons) into the dentate gyrus inner molecular layer. In this review, we highlight the role of mossy fiber sprouting in seizure generation and hippocampal excitability and discuss the responses of alternative treatment strategies in terms of MFS and spontaneous recurrent seizures in models of TLE.